1995
DOI: 10.1007/bf00121916
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of cancer cell motility and invasion by interleukin-12

Abstract: Tumour cell motility and attachment are crucial requirements in the formation of metastatic lesions. These properties are affected by a number of cytokines including hepatocyte growth factor/scatter factor (HGF/SF) and several immunoregulatory proteins, including interleukin-12 (IL-12). Although IL-12 has been reported to exhibit potent anti-tumour effects in vivo, a direct effect of IL-12 on cancer cells has not been reported. We show here that IL-12 directly inhibited the attachment of the human colon cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1

Year Published

1998
1998
2004
2004

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 38 publications
1
17
1
Order By: Relevance
“…26) IL-12 and g-linolenic acid inhibit HGF-induced tumor migration via up-regulation of cell-surface Ecadherin. 27,28) IL-4 is also shown to inhibit HGF-induced tumor migration but its mechanism is unknown. 29) In contrast, evodiamine suppressed HGF-induced tumor migration by acting to repress the cell spreading.…”
Section: -4)mentioning
confidence: 99%
“…26) IL-12 and g-linolenic acid inhibit HGF-induced tumor migration via up-regulation of cell-surface Ecadherin. 27,28) IL-4 is also shown to inhibit HGF-induced tumor migration but its mechanism is unknown. 29) In contrast, evodiamine suppressed HGF-induced tumor migration by acting to repress the cell spreading.…”
Section: -4)mentioning
confidence: 99%
“…We and others have demonstrated that 3T3-CM, which is used as a chemoattractant in the Matrigel invasion chamber assay, contains a number of motility factors that increase the invasiveness of breast cancer cells [5,6]. Since cellular motility is known to be directed by chemotactic motility factors and secreted cytokines [2,3], the present study examined the hypothesis that 3T3-CM contains specific factors that enhance the motility of breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…The metastatic dissemination of tumor cells to secondary sites requires highly motile cancer cell behavior which appears to be influenced by growth factors, cytokines, and other molecules yet to be identified [2,3]. We and others have demonstrated that 3T3-CM, which is used as a chemoattractant in the Matrigel invasion chamber assay, contains a number of motility factors that increase the invasiveness of breast cancer cells [5,6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…*: p Ͻ 0.001, as compared with control by Student's two-tailed t test. cyte growth factor (HGF)-induced motility of human colon cancer cell lines HRT 18, HT 29 and HT 115 (Hiscox et al, 1995). Isoai et al (1992) have observed that tumor invasion-inhibiting factor-2 (IIF-2) purified from bovine liver could inhibit chemotaxis of murine B16-FE7 melanoma cells to fibronectin or laminin, invasion through Matrigel and experimental lung metastasis in mice.…”
Section: Discussionmentioning
confidence: 99%